Strategi Pemasaran Sosis Obong Dendra melalui Media Sosial Facebook - Riska Puspita Dewi; Muhammad Iqbal Fasa (MAMEN: Jurnal Manajemen, 2024)
This study analyzes the methods and techniques of product marketing through social media, with a special focus on its impact on sales and brand awareness. This study takes the example of the business "Sosis Obong Dendra," which uses Facebook as the main platform to interact with customers, and has more than 1000 friends on the network. The research method used is descriptive qualitative with a case study approach, which allows for an in-depth exploration of the marketing practices implemented. The results of the study indicate that the use of social media effectively increases brand visibility and allows for direct interaction with customers. This interaction not only builds positive relationships but also strengthens brand loyalty among consumers. The findings show that this marketing strategy has succeeded in increasing sales, especially among the millennial generation who are active on digital platforms. In addition, the ability to understand customer needs and preferences through direct interaction increases engagement and satisfaction. This study confirms that social media is an important strategic tool in creating an engaging and personalized customer experience, as well as in building strong brand awareness in an increasingly competitive market. These findings provide valuable insights for business actors in formulating more effective marketing strategies.